2010
DOI: 10.1038/hr.2010.102
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the L-arginine–NO–cGMP pathway in spontaneously hypertensive rat platelets: the effects of pregnancy

Abstract: Nitric oxide (NO) is a short-lived intercellular messenger that provides an efficient vascular regulatory mechanism to support homeostasis and prevent thrombosis. Endothelial dysfunction and reduced NO bioavailability have a central role in hypertension associated with pregnancy. The purpose of this study was to investigate the impact of pregnancy on the L-arginine-NO-cGMP pathway in platelets and its correlation to platelet function and blood pressure in normotensive rats and spontaneously hypertensive rats (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
3
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 51 publications
(48 reference statements)
0
3
0
Order By: Relevance
“…Arginine is the physiological precursor of NO, and it forms NO after catalyzed by NO synthase (Ognibene et al, 2010). Exogenous arginine is one of the ways to enhance the content of NO (Yurkiv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Arginine is the physiological precursor of NO, and it forms NO after catalyzed by NO synthase (Ognibene et al, 2010). Exogenous arginine is one of the ways to enhance the content of NO (Yurkiv et al, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…The levels obtained from SHR-P were not significantly different from those of the normotensive groups, which is in agreement with previous findings. 15,17 These results might be partially explained by an increased production of NO and PGI 2 from vascular endothelium 25 and hyporeactivity to vasoconstrictors 5 which may contribute to vasodilation and consequent reduction in peripheral vascular resistance. It is widely accepted that an excess of NO is generated by endothelial cells during normal pregnancy.…”
Section: Discussionmentioning
confidence: 93%
“…Recently, it was demonstrated that inducible NOS (iNOS) or endothelial NOS (eNOS) are present neither in mouse nor in human platelets [ 36 ]. However, various works have shown the presence of eNOS/NO/sGC/cGMP signaling in platelets using by different experimental approaches including aggregation assays in presence of sGC and eNOS inhibitors [ 37 ], western blotting for eNOS [ 38 , 39 ], [ 3 H]L-citrulline [ 40 ] and cGMP production [ 37 , 38 ]. Therefore, in the present work we decided to investigate the role of sGC/cGMP/PKG pathway in the inhibitory effect of LPS-injection on platelet aggregation.…”
Section: Discussionmentioning
confidence: 99%